Buskers to Tourists in Bukittinggi City - Fadhlan Azim; Selvi Kasman; Yade Surayya (Kirana Publisher (KNPub), 2024)
This study discusses the unpleasant actions of buskers towards tourists in the city of Bukittinggi. The purpose of this study was to see the unpleasant actions of buskers towards tourists in the city of Bukittinggi. The research method used is qualitative research. Data collection techniques include field observations, interviews, and documentation. The theory used is the theory of differential association by Sutherland. The findings in this study are several unpleasant actions towards tourists in the tourist attraction area, as for the factors behind these actions are, the lack of busker education levels, environmental factors and low economic levels. Unpleasant actions against tourists such as forcing visitors to give money, and acts of harassment against tourist visitors in the city of Bukittinggi. This incident is often experienced by tourists who are on vacation in Jam Gadang, to overcome this, the security of the city of Bukiitinggi immediately intervened to the tourist site, to overcome these cases, so that tourists present in the city of Bukittinggi feel more safe and peaceful while traveling to the city of Bukittinggi.